The island and the ring - Stevenson, Laura Caroline 1946- (Houghton Mifflin, 1991)
After treachery destroys her kingdom, Princess Tania discovers that it is her destiny to confront Ascanet, the ruthless lord enslaving the island of Elyssonne.